Estrategia general del mejoramiento genetico del frijol en el CIAT - Temple, Steven R. (International Center for Tropical Agriculture, 1979)
CIATs bean improvement program has the objective of generating and fomenting the production of high-yielding materials and extensive combinations of resistance to factors that adversely affects the production of the crop. The general strategy is to (a) make bean cultivation more productive, profitable and reliable, (b) increase the physiological potential to yield and (c) identify limiting production factors through an international network of specialists. Other directions taken by the program are to increase the no. of progeny and crosses, the use of agroeconomic data to define priorities, progressive selection of characters resistant to insects, pathogens and adverse environmental conditions, separation of climbing and bush beans, and the extensive use of the bean information system (SIFRI) at a national and international level. Key aspects of the bush bean breeding program are also defined and considerations are given on the priorities of the incorporation of disease-resistance. (CIAT)